(untitled) (O Cosmopolítico, 2014)
This research seeks to historically contextualize contemporary China-Russia relations, which in 2013 witnessed important developments in the post-Cold War period. The study highlights that focus of the current improvement of ties between the two countries is different from that of the past. Whereas in the 1950s it was the economic aid and ideological conflict, today economy and security dominate the Sino-Russian linkage.